Histomorphological and inflammatory changes of white adipose tissue in gastrointestinal cancer patients with and without cachexia. Issue 1 (22nd December 2021) - Molfino, Alessio; Carletti, Raffaella; Imbimbo, Giovanni; Amabile, Maria Ida; Belli, Roberta; di Gioia, Cira R.T.; Belloni, Elena; Spinelli, Francesco; Rizzo, Veronica; Catalano, Carlo; Nigri, Giuseppe; Muscaritoli, Maurizio
Abstract: Background: During cancer cachexia, several alterations occur in peripheral tissues, and the adipose tissue may be involved during the catabolic state. We aimed at investigating histological rearrangement and infiltration of inflammatory cells in subcutaneous adipose tissue (SAT) of patients with cancer undergoing surgery, according to the presence/absence of cachexia. Methods: We considered gastrointestinal cancer patients and controls with non‐malignant diseases undergoing surgery. We collected SAT samples and performed histomorphological analyses [cross‐sectional area (CSA) and per cent of fibrosis] and immunohistochemistry to characterize the inflammatory cells. By computed tomography (CT) scan, we calculated SAT and visceral adipose tissue (VAT). Results: We enrolled 51 participants (31 gastrointestinal cancer patients and 20 controls). In cancer patients, cachexia was present in 13/31 (42%). The CSA (μm 2 ) of the adipocytes from SAT was reduced in cancer patients vs. controls (3148, inter‐quartile range 2574–3755 vs. 4474, inter‐quartile range 3654–5183) ( P < 0.001), in particular in cachectic patients vs. non‐cachectic (median 2518 vs. median 3470) ( P = 0.03) and in cachectic vs. controls ( P < 0.001), as well as in non‐cachectic vs. controls ( P = 0.04). The median per cent of fibrosis was higher in cancer patients vs. controls (9 vs. 3) ( P = 0.0001), in particular in cachectic vs. non‐cachectic (13.35 vs. 7.13) ( P = 0.03). We observed a higher number of macrophages (CD68) ( P = 0.0001) and T lymphocytes (CD3) ( P = 0.002) in SAT of cancer patients vs. controls, and the number of T lymphocytes was higher in cachectic vs. non‐cachectic patients ( P = 0.025). Anorexic cancer patients showed in SAT a higher number of macrophages and T lymphocytes with respect to controls ( P < 0.0001), whereas no difference was present between anorexic and non‐anorexic patients. At CT scan, cachectic patients showed lower VAT and SAT vs. non‐cachectic (VAT: 97.64 ± 40.79 vs. 212.53 ± 79.24, P = 0.0002; SAT: 126.27 ± 87.92 vs. 206.27 ± 61.93, P = 0.01, respectively). Cancer patients with low CSA, high degree of fibrosis, and high number of T lymphocytes presented with lower body mass index and lower SAT and VAT at CT scan ( P ≤ 0.01). Conclusions: We found histological alterations of SAT among gastrointestinal cancer patients and in particular significant changes in CSA, fibrosis, and inflammation when cachexia was present; the changes in histomorphological parameters of the adipocytes reflected alterations in adiposity at body composition analysis.